Creating a learning to learn school : research and practice for raising standards, motivation and morale. - Greany, Toby (Continuum International Pub. Group, 2003)
Creating a learning to learn school is a book for heads, senior managers and teachers interested in developing better schools, classrooms and learners. The book sets out: why 'learning to learn' is important; the implications of learning to learn for the government's educational reforms; what is meant by learning to learn; the findings from the Campaign for Learning's learning to learn research project; how heads and teachers can develop learning to learn in their own schools. Click here to access the colour poster Do you know how you learn best? . This sets out the 5Rs for learning and is int.